The Effectiveness of Contract Control for the Procurement of Goods and Services at the Secretariat General of the Constitutional Court - Muhammad Rizki; R. Luki Karunia (Eduvest - Journal of Universal Studies, 2026)
Contract control in government procurement is a critical determinant of the quality of public expenditure. However, recurring audit findings related to volume shortages, overpayments, and non-compliance indicate persistent weaknesses in contract control across Indonesian public institutions. This study aims to analyze the effectiveness of contract control in the procurement of goods and services at the Secretariat General of the Constitutional Court. Contract control is essential for ensuring that procurement activities are conducted in accordance with applicable regulations while meeting requirements related to time, quality, cost, and organizational objectives. In practice, effective contract control extends beyond administrative compliance to include monitoring contract implementation, verifying compliance with technical specifications, mitigating risks, and addressing issues that arise during contract execution. This study employed a qualitative descriptive approach, with data collected through observation, interviews, and document analysis. The analysis examined the effectiveness of contract control throughout the procurement process, including the planning, implementation, monitoring, evaluation, and contract completion stages. The findings indicate that effective contract control is strongly influenced by comprehensive planning, competent human resources, effective inter-unit coordination, regulatory compliance, and the use of a structured monitoring system. Well-implemented contract control minimizes project delays, non-compliance with technical specifications, contractual disputes, and the risk of financial losses to the state. Therefore, contract control within the procurement of goods and services at the Secretariat General of the Constitutional Court should be implemented consistently, transparently, and accountably to support the principles of good governance.